INNOVATIVE LEARNING BY UTILIZING WORDWALL TO MAKE IT INTERACTIVE IN ELEMENTARY SCHOOL - Susanti; Ghulam Hamdu; Karlimah Karlimah (Universitas Majalengka, 2025)
This research aims to analyze the effectiveness of using Wordwall, a gamification-based platform, in improving elementary school students' critical thinking skills on Solar System materials. This is motivated by the fact that digital transformation in basic education has encouraged the utilization of technology to increase student engagement and interactivity, but there are still many challenges in delivering materials in an interesting and effective way. On the other hand, although students show interest in Solar System materials, they often struggle in understanding abstract concepts such as revolution, rotation and gravity. Conventional learning is often not interactive enough, so students feel less engaged and have difficulty in understanding the material. The use of innovative educational technology such as Wordwall is expected to address this issue, by offering a more engaging and fun approach to learning complex concepts. This study used a qualitative approach with exploratory descriptive method, involving interviews, questionnaires and observations of three teachers and 30 students in three elementary schools that have adopted technology-based learning. The results showed that students using Wordwall were more active in discussions and had better understanding compared to conventional learning methods. Therefore, Wordwall has great potential to improve learning effectiveness and students' critical thinking skills in elementary schools. The results of this study are expected to be a reference for educators in optimizing the use of technology in more innovative and effective learning.